The Binding Problem 2.0: Beyond Perceptual Features. Issue 2 (6th February 2023) - Yu, Xinchi; Lau, Ellen
Abstract: The "binding problem" has been a central question in vision science for some 30 years: When encoding multiple objects or maintaining them in working memory, how are we able to represent the correspondence between a specific feature and its corresponding object correctly? In this letter we argue that the boundaries of this research program in fact extend far beyond vision, and we call for coordinated pursuit across the broader cognitive science community of this central question for cognition, which we dub "Binding Problem 2.0".